2006
DOI: 10.1080/03630260600868071
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Molecular Basis of Hemoglobinopathies in Cambodia

Abstract: Blood counts, hemoglobin (Hb) high performance liquid chromatography (HPLC), and DNA analyses were performed on 260 children, aged 5 months to 16 years, at Siem Reap to assess the prevalence of thalassemia and other hemoglobinopathies in regional Cambodia. Hemoglobinopathies were present in 134 children (51.5%) with 20 abnormal genotypes identified. alpha-Thalassemia (thal) (35.4%) was the most prevalent disorder and the -alpha3.7 gene deletion was the most common alpha-globin gene abnormality. The - -SEA dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…11,18 Up to 25-35% of Thai and Cambodian people are carriers of a-thalassemia, and up to 60% of Thai and Cambodian people are carriers of hemoglobin E. 11,36 Although the heterozygotes for a-thalassemia 1, b-thalassemia, and HbE typically are asymptomatic, they may cause mild microcytic, hypochromic anemia. 18 In this study, we used the most reliable method (DNA analysis) to detect common thalassemia mutations or deletions of a-and b-genes and found that 125/299 (41.8%) of the study population had underlying thalassemia (Table 3), mainly the thalassemia trait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,18 Up to 25-35% of Thai and Cambodian people are carriers of a-thalassemia, and up to 60% of Thai and Cambodian people are carriers of hemoglobin E. 11,36 Although the heterozygotes for a-thalassemia 1, b-thalassemia, and HbE typically are asymptomatic, they may cause mild microcytic, hypochromic anemia. 18 In this study, we used the most reliable method (DNA analysis) to detect common thalassemia mutations or deletions of a-and b-genes and found that 125/299 (41.8%) of the study population had underlying thalassemia (Table 3), mainly the thalassemia trait.…”
Section: Discussionmentioning
confidence: 99%
“…13 IDA [3][4][5][6][7][8][9][10][11][12][13][14][15] was defined as anemia with (1) serum ferritin < 10 lg/ml if CRP was < 10 mg/liter or serum ferritin < 50 lg/ml if CRP was ‡ 10 mg/liter 16,17 and (2) having at least three of the following five parameters: (1) SI < 8.8 lmol/liter, (2) TIBC > 71.6 lmol/liter, (3) TS < 10%, (4) mean corpuscular volume (MCV) less than normal age-related values ( < 2 years = 78 fl, ‡ 2 years = 81 fl), or (5) mean corpuscular hemoglobin (MCH) less than normal age-related values ( < 2 years = 23 pg, 2-5 years = 24 pg, and ‡ 6 years = 25 pg). 14,15 Nonthalassemia was defined as having no common thalassemia mutations or deletions of a-and b-genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, anemia of this type is also associated with both vitamin A deficiency (3) and genetic Hb 11 disorders that affect the structure, function and/or production of Hb (4). The occurrence of both of these conditions is well documented in Cambodian children (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Two genetically distinct variants are common: Hb E and a-thalassemia (6,9); their frequency varies with geographic region. Hb E disease arises from a genetic alteration in the physical structure of Hb, specifically a single amino acid substitution in one of the bglobin chains.…”
Section: Introductionmentioning
confidence: 99%